فلسفہ، سائنس اور مذہب کا باہمی فرق، تعامل اور اقبال کا فلسفہ علم - Ahmad, Nazir (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2026)
This paper examines the historical and theoretical differences and connections between philosophy, science and religion, focusing on the different aims and methods of these three fields of knowledge and understanding. It traces the roots of science in natural philosophy, examining their corresponding roles in research, through the study of the historical background of philosophy and science. It then talks about the shared basis and the controversies between philosophy and religion, and explains the unique purpose of religion in specifying the relationship between Creator and creation. This paper takes the view that science should be seen as a means and not as an end in accordance with the hierarchical system of philosophical research. Moreover, this paper highlights the supremacy of religious teachings in relation to the reality and meaning of ethics and values, arguing that religious awareness is stronger, more meaningful and based on realization than intellectual awareness alone, which is why the system of ethics offered by religion is always superior. The problem of the relationship between religion, philosophy and science was a subject of special interest to Allama Iqbal. Although he also discussed this issue in his philosophical poetry, he presented it rigorously in his philosophical book “The Reconstruction of Religious Thought in Islam.” In exploring the complex relationship between religion, philosophy and science, this article also focuses on this masterpiece of Allama Muhammad Iqbal. This article is an attempt to concisely analyze Allama Iqbal’s views on religion, philosophy and science in the context of his philosophical discourse. The interpretation of scientific principles in the light of Islamic thought, and the analysis of Allama’s vision on the evolution of religious thought are important parts of the subject of this article in which an attempt has been made to find out how these three different fields of knowledge can be harmonized in the search for universal knowledge and what significance Iqbal’s thoughts have in the current debates on this journey. The structure of the reconstruction of Islamic thought stands on three important pillars: metaphysics, the concept of knowledge, and law. Focusing on Iqbal’s concept of knowledge, an attempt has been made to shed light on his metaphysical and theological philosophy of knowledge. However, the conclusion of this paper emphasizes the need to maintain a clear distinction and an atmosphere of cooperation between different fields of knowledge in order to promote the pursuit of knowledge.